Differences in Labor Outcomes for Mothers with Regular and Irregular Antenatal Care (ANC) - Iin Erliyana Elias; Mardiana Ahmad; Sharvianty Arifuddin; Farid Husin; Stang Stang; Werna Nontji (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The occurrence of labor complications can be prevented by carrying out treatments such as carrying out antenatal care (ANC) during pregnancy. The study was conducted to determine the differences in birth outcomes between Regular and Irregular antenatal care (ANC). This was an analytical observational study using a prospective cohort approach involving 44 pregnant women, who were recruited between January and April 2022 at the Barana Health Center, Jeneponto Regency. The research instrument used was the observation sheet. Data analysis used analytical test (Mann-Whitney and unpaired T test). There was a significant difference between regular and irregular ANC with length of stage I (multipara and grande multipara) p-value=0,040, baby's birth weight (p-value=0,047), baby's body length (p-value=0,009), and baby's chest circumference (p-value=0,009) (p-value<0,05). Whereas in regular and irregular ANC with the length of the first stage (primipara) (p-value=0,958) and the newborn head circumference (value=0,141) illustrates that there was no significant difference (p-value>0,05). Pregnant women with regular ANC tend to have birth outcomes with a longer first stage (multipara and grande multipara), weight, body length, and chest circumference of normal newborns compared to pregnant women with irregular ANC.